NEXT WAR : REIMAGINING HOW WE FIGHT - Antal, John (Casemate Publishers, 2023)
The nature of war is constant change. We live in an era of exponential technological acceleration which is transforming how wars are waged. Today, the battlespace is transparent; multi-domain sensors can see anything, and long-range precision fire can target everything that is observed.Autonomous weapons can be unleashed into the battlespace and attack any target from above, hitting the weakest point of tanks and armoured vehicles. War now develops at hyper-speed, risking operational, informational, and organisational paralysis induced by the rapid convergence of key disrupters in the battlespace. Hit with too many attacks in multiple domains, all occurring simultaneously, the force is paralysed.